Piquetes como repertório: organização operária e redes sociais nas greves de 1957 e 1980 - Fontes, Paulo (2017)
This article analyzes the role of pickets in two of the most emblematic strikes in Brazilian labor history: the 'strike of the 400,000,' which involved several industry sectors in São Paulo and neighboring cities in 1957, and the 1980 'forty-one days strike,' involving the metalworkers of the ABC Paulista, in the metropolitan area of the city of São Paulo. Both strikes broke out at a time of profound reconfiguration of Brazilian society, marked by the processes of industrialization, migration, and urbanization. Although separated by a time gap of almost twenty-five years, both the 'strike of the 400,000' and the 'forty-one days strike' reveal important aspects of continuities in the performances and the organizational repertoires of the workers in São Paulo.